Exploring candidate interaction with a high stakes teacher performance assessment: The KPTP and the Kansas laboratory - Connor K. Warner (Education Policy Analysis Archives, 2020)
This qualitative study explores the experiences of a cohort of pre-service teachers completing a high-stakes teacher performance assessment (HSTPA), the Kansas Performance Teaching Portfolio (KPTP), during their final year of teacher preparation. The inquiry asks whether the act of completing the assessment modified candidate conceptualizations of good teaching, and, if so, in what ways. Data were gathered via in-depth interviews and content analysis, and data were analyzed via constant comparison. The study found that completing the KPTP was having some impact upon participant conceptions of good teaching, prodding them to broaden their understanding of the work of teachers to include not just dispositional and relational aspects of teaching, but elements of technical teaching practice. The article concludes with recommendations for policy, research, and practice.